Extended Printmaking: (Im)Pure Print practices | Gravura prolongada: Práticas impuras - Machado, Graciela; Bełkot, Marta (Pós-Limiar | Título não-corrente, 2019)
This article seeks to reveal how the Pure Print International Printmaking Meeting may contribute with new insights towards the current quest for a relevant printmaking practice. The meeting was converted into a research platform, allowing a compilation and experiment with our desire for a full printmaking experience. Refusing a linear technological progression and rigid research plans, we moved into an impure practice seen as a transition into an intermedia experience. Slowly, we embarked on a series of experiments to pursue processes that have the potential of a photographic reproduction and looked back at a past where terms as “chemical printing” referred to the print capacity to literally transfer a drawing as first found in stone lithography. In the end, multiple technological incursions and cross academic contributions confirmed how printing research may be used to make the production of contemporary artistic printing practices easier and expand their aesthetic possibilities. Moreover, the modes of production employed reinforce perceptions of how context, conditions, and processes must be set up for a creative, resolutive, and innovative research to take place. By emphasizing the use of local resources, aligning craft and practice, and selecting connections between printmaking and creative practices at large, we shed new light on how printmakers may construct knowledge.